Aromatherapy vs. Acupressure for Pregnancy Nausea Efficacy: Aromaterapi vs Akupresur untuk Khasiat Mual pada Kehamilan - Nissa Nahdiana; Siti Cholifah (Universitas Muhammadiyah Sidoarjo, 2024)
Nausea and vomiting afflict many pregnant women, particularly in the first trimester, prompting interest in non-pharmacological remedies like citrus lemon aromatherapy and PC6 acupressure massage. Yet, comparative studies on their effectiveness remain scarce. This research aimed to assess the efficacy of these interventions in reducing nausea and vomiting among first-trimester pregnant women with emesis gravidarum. Using a quasi-experimental design, two groups of participants received either citrus lemon aromatherapy or PC6 acupressure massage. The PUQE-24 scale measured symptoms before and after the interventions. Results indicated significant reductions in symptoms for both groups (p < 0.05), with no significant difference in effectiveness between the interventions (p = 0.465). These findings underscore the potential of non-pharmacological therapies to alleviate pregnancy-related nausea and vomiting, suggesting their integration into prenatal care practices for improved maternal well-being. Highlight: Non-drug Relief: Citrus lemon aromatherapy and PC6 acupressure massage. First-Trimester Aid: Efficacy for pregnancy-induced nausea and vomiting. Equal Effectiveness: Aromatherapy versus acupressure for symptom reduction. Keyword: Nausea, vomiting, pregnancy, aromatherapy, acupressure